Assessing the diversity and intensity of pesticide use in communal area cotton production in Zimbabwe - W. Mubvekeri; J. Bare; Caston Makaka; F. Jimu (Academic Journals, 2023)
A survey was conducted in Checheche, Nemangwe, Sanyati and Tafuna areas of Zimbabwe to assess the level of insecticide use and use of protective clothing in smallholder cotton production areas where the Cotton Research Institute conducted cotton experiments. Compliance with the closed season legislation, the Plant Pest and Diseases Act, Chapter 19, Section 8 of 1988 was checked because of its role in seasonal pest survival. Generally, pest management was found to be anchored on the use of insecticides with 71.9% of the farmers having positive indications regarding dependence on insecticides for pest control. Fifty nine percent of the farmers did not use scouting as a method to determine the need to spray insecticides. The closed season that helps break life cycle of insects was predominantly not observed. Integrated pest management approaches need to be promoted for the sack of the environment and the future of humanity.